Study on coal ash loaded nano iron filler to improve the efficient phosphorus removal of biological detention facility - Zhang, Yuxuan; Gao, Xueqin; Zhang, Lulu; He, Shunde (Frontiers in Environmental Science, 2022)
Bioretention cells are an important facility to solve the hydrological and non-point pollution problems in urban areas, especially phosphorus. In this paper, ceramsite composite was made from coal ash and modified by nano-iron through coprecipitation and reduction, which was used to remove the phosphorus in the water. The results of the characteristics of the ceramsite composite using scanning electron microscope showed that the surface of the ceramsite loaded with nano-iron became rougher and the iron nanoparticles were uniformly distributed on the surface, and there was no obvious agglomeration of nano-iron particles. The loading effect was good and the activity of the ceramsite was greatly improved. The results from the static and dynamic continuous experiments indicated that the modified ceramsite with nano-iron had a good removal effect on phosphorus, and the removal rate reached over 99%. The results of this study can provide a new way for the resource utilization of coal ash, and also inspires a new idea for the improvement of filler in bioretention facilities.